Analysis of Partial Thromboplastin Times in Patients With Pulmonary Embolism During the First 48 Hours of Anticoagulation With Unfractionated Heparin. (24th November 2019) - Prucnal, Christiana K.; Jansson, Paul S.; Deadmon, Erin; Rosovsky, Rachel P.; Zheng, Hui; Kabrhel, Christopher
Abstract: Objective: The objective was to determine the proportion of patients with pulmonary embolism (PE) treated with unfractionated heparin (UFH) who achieved therapeutic activated partial thromboplastin time (aPTT) values within 48 hours of treatment. Methods: Retrospective analysis of a PE response team (PERT) database was performed at a large, urban, academic teaching hospital. Inclusion criteria were adult patients with acute PE for whom the PERT was consulted and who received anticoagulation (AC) with UFH according to guideline standard dosing. aPTT values during 6‐hour time periods during the first 48 hours of AC were collected and analyzed. Results: A total of 505 patients met inclusion criteria. For patients receiving a bolus and infusion of UFH, the proportions (95% confidence interval [CI]) of patients in the therapeutic range were 19.0% (14.2% to 25.0%) at 12 hours, 26.3% (26.3% to 33.1%) at 24 hours, 28.3% (22.0% to 35.4%) at 36 hours, and 28.4% (20.8% to 37.5%) at 48 hours. For titrated infusion only, the proportions (95% CIs) of patients were 23.3% (16.2% to 32.3%) at 12 hours, 41.4% (31.6% to 51.9%) at 24 hours, 37.0% (26.8% to 48.5%) at 36 hours, and 42.1% (30.2% to 55.0%) at 48 hours. No patient had all therapeutic aPTT values. Conclusions: The majority of patients with acute PE spend most of their first 48 hours outside of the therapeutic range of AC when treated with guideline standard dosing of UFH. Over half of the patients fail to achieve any therapeutic PTT level within 24 hours of UFH initiation, and no patient had all therapeutic aPTTs. Future research should focus on identifying factors associated with achieving therapeutic AC with UFH.